VALIDATION OF A CUSTOMIZED QUESTIONNAIRE TO ASSESS COMMUNITY PHARMACISTS’ KNOWLEDGE, PERCEPTIONS AND BARRIERS IN PROVIDING PHARMACEUTICAL CARE: A PILOT STUDY - Shalini Rawat; Yogesh Joshi (The Bioscan, 2025)
A community pharmacist plays an important role between physicians and patients. In the healthcare system by serving as the most accessible healthcare professional to the public they are responsible for ensuring that patients receive optimal pharmaceutical care. A pilot study involving current community pharmacist services in various districts of Uttarakhand was conducted to validate a customized questionnaire. The questionnaire encloses a total number of 29 questions designed to determine community pharmacist attitudes and perceptions of barriers to providing pharmaceutical care. The questionnaire focused – on demographic data, essential pharmaceutical care skills of a community pharmacist working in a community pharmacy, and other factors related to patient treatment. The researcher visited randomly selected 50 community pharmacists working in community pharmacy setups in the Uttarakhand state. The reliability of the questionnaire was measured using Cronbach’s alpha, which produced a value of 0.82, indicating good reliability and consistency. Pharmacy practitioners working in community pharmacies in Uttarakhand are actively engaged in the delivery of pharmaceutical care to patients. We suggest improving and implementing communication and interaction between the pharmacist, other healthcare professionals, and patients. We improve to drive change because community pharmacists showed a strong interest amongst them to learn more and providing adequate and beneficial pharmaceutical care for patients. Our study will help us understand the challenges faced by community pharmacists in the various districts.